Metal Alloys for Fusion‐Based Additive Manufacturing. Issue 5 (1st February 2018) - Zhang, Duyao; Sun, Shoujin; Qiu, Dong; Gibson, Mark A.; Dargusch, Matthew S.; Brandt, Milan; Qian, Ma; Easton, Mark
Abstract : Metal additive manufacturing (AM) is an innovative manufacturing technique, which builds parts incrementally layer by layer. Thus, metal AM has inherent advantages in part complexity, time, and waste saving. However, due to its complex thermal cycle and rapid solidification during processing, the alloys well suit and commercially used for metal AM today are limited. Therefore, it is important to understand the alloying strategy and current progress with materials performance to consider alloy development for metal AM. This review presents the current range of alloys available for metal AM, including titanium, steel, nickel, aluminum, less common alloys (including Mg alloys, metal matrix composites alloys, and low melting point alloys), and compositionally complex alloys (including bulk metallic glasses and high entropy alloys) with a focus on the relationship between compositions, processing, microstructures, and properties of each alloy system. In addition, some promising alloy systems for metal AM are highlighted. Approaches for designing and optimizing new materials for metal AM have been summarized. Abstract : Additive manufacturing is characterized by rapid solidification and complex thermal cycles during processing, which means the alloys well suit and commercially used for additive manufacturing are limited. This review presents the current range of alloys available for metal additive manufacturing. More importantly, alloying design strategy and some promising alloy systems for metal additive manufacturing are highlighted.